Recent Advances and Contradictions in the Study of the Individual Roles of Ubiquitin Ligases That Regulate RIG-I-Like Receptor-Mediated Antiviral Innate Immune Responses - Oshiumi, Hiroyuki (Frontiers in Immunology, 2020)
RIG-I and MDA5 are cytoplasmic viral RNA sensors and are essential for antiviral innate immune responses, such as type I interferon production. Post-translational modification is critical for the activation and inactivation of RIG-I and MDA5. At least seven ubiquitin ligases have been reported to be involved in either K63- or K48-linked polyubiquitination of RIG-I and MDA5, and these ubiquitin ligases are further regulated by other factors. TRIM25 is an E3 ubiquitin ligase that delivers a K63-linked polyubiquitin moiety to the caspase activation and recruitment domains (CARDs) of RIG-I, thereby activating the antiviral innate immune response. Recent studies have shown that NDR2, ZCCHC3, and Lnczc3h7a promote TRIM25-mediated RIG-I activation. Riplet is another ubiquitin ligase that mediates the K63-linked polyubiquitination of the C-terminal domain (CTD) of RIG-I; however, it was also reported that Riplet delivers the K63-linked polyubiquitin moiety to the CARDs of RIG-I as well as to the CTD, thereby activating RIG-I. Further, there are several factors that attenuate the activation of RIG-I and MDA5. RNF125, TRIM40, and c-Cbl mediate K48-linked polyubiquitination and induce degradation of RIG-I and/or MDA5. USP21 and CYLD remove the K63-linked polyubiquitin chain from RIG-I, and NLRP12 inhibits polyubiquitin-mediated RIG-I activation. Although these new regulators have been reported, their distinctive roles and functional differences remain elusive, and in some cases, studies on the topic are contradictory to each other. In the present review, recent studies related to post-translational modifications of RIG-I and MDA5 are summarized, and several controversies and unanswered questions in this field are discussed.